Matrices based on lineal and star fumarate-metha/acrylate copolymers for bone tissue engineering: Characterization and biocompatibility studies - Bravi Costantino, Maria Leticia (2019)
This article presents the preparation of matrices from two new families of fumaric copolymers and the effect of structural differences on their physicochemical and biological behavior. Diisopropyl fumarate (DIPF) and poly(ethylene glycol) methyl ether methacrylate (OEGMA) or N-isopropylacrylamide (NIPAM) were copolymerized by conventional radical and RAFT polymerization to obtain lineal or start architectures, respectively. These copolymers were characterized by spectroscopic (FTIR and ¹HNMR) and chromatographic methods. The thermal stability was studied by thermal gravimetric analysis, showing some differences in relation to the architecture and chemical nature of copolymers. SEM morphological analysis demonstrated that the surface of the matrices derived from OEGMA exhibited an irregular and rough surface, while DIPF–NIPAM copolymers presented smooth surface with nearly no significant porosity. The matrix obtained of both kinds of copolymers presented no cytotoxicity as it was evaluated using a model of macrophages on culture. Moreover, cell growth was better on the surfaces of the DIPF–NIPAM matrices, suggesting a good interaction with this matrix and its potential application as matrices for tissue engineering.